Rare Hepatic Arterial Anatomic Variants in Patients Requiring Pancreatoduodenectomy and Review of the Literature. (30th July 2012) - Ramanadham, Smita; Toomay, Seth M.; Yopp, Adam C.; Balch, Glen C.; Sharma, Rohit; Schwarz, Roderich E.; Mansour, John C.
Abstract : Normal hepatic arterial anatomy occurs in approximately 50–80% of cases; for the remaining cases, multiple variations have been described. Knowledge of these anomalies is especially important in hepatobiliary and pancreatic surgery in order to avoid unnecessary complications. We describe two cases of patients undergoing pancreatoduodenectomy for abnormalities in the head of the pancreas. Preoperative contrast-enhanced cross-sectional imaging demonstrated relevant, rare hepatic arterial variants: (1) a completely replaced hepatic arterial system with a gastroduodenal artery (GDA) arising directly from the celiac axis and (2) a replaced right hepatic artery originating from the superior mesenteric artery and traveling anterior to the pancreatic uncinate process and head. These findings were confirmed during pancreatoduodenectomy. Both of these variants have been rarely described with an incidence of <1.0%. In the present paper, we describe the hepatic arterial anomalies commonly encountered and clarify the important details associated with these variants as they pertain to pancreatoduodenectomy.